Therapeutic and Prognostic Implications of BRAF V600E in Pediatric Low-Grade Gliomas - Lassaletta, Alvaro; Zapotocky, Michal; Mistry, Matthew; Ramaswamy, Vijay; Honnorat, Marion; Krishnatry, Rahul; Guerreiro Stucklin, Ana; Zhukova, Nataliya; Arnoldo, Anthony; Ryall, Scott; Ling, Catriona; McKeown, Tara; et al. (Journal of clinical oncology, 2017)
Purpose BRAF V600E is a potentially highly targetable mutation detected in a subset of pediatric low-grade gliomas (PLGGs). Its biologic and clinical effect within this diverse group of tumors remains unknown. Patients and Methods A combined clinical and genetic institutional study of patients with PLGGs with long-term follow-up was performed (N = 510). Clinical and treatment data of patients with BRAF V600E mutated PLGG (n = 99) were compared with a large international independent cohort of patients with BRAF V600E mutated-PLGG (n = 180). Results BRAF V600E mutation was detected in 69 of 405 patients (17%) with PLGG across a broad spectrum of histologies and sites, including midline locations, which are not often routinely biopsied in clinical practice. Patients with BRAF V600E PLGG exhibited poor outcomes after chemotherapy and radiation therapies that resulted in a 10-year progression-free survival of 27% (95% CI, 12.1% to 41.9%) and 60.2% (95% CI, 53.3% to 67.1%) for BRAF V600E and wild-type PLGG, respectively ( P < .001). Additional multivariable clinical and molecular stratification revealed that the extent of resection and CDKN2A deletion contributed independently to poor outcome in BRAF V600E PLGG. A similar independent role for CDKN2A and resection on outcome were observed in the independent cohort. Quantitative imaging analysis revealed progressive disease and a lack of response to conventional chemotherapy in most patients with BRAF V600E PLGG. Conclusion BRAF V600E PLGG constitutes a distinct entity with poor prognosis when treated with current adjuvant therapy.
Keywords: Brain Neoplasms; gliom; Male; kohortové studie; mutace; Child, Preschool; Cohort Studies; Neoplasm Grading; Adolescent; nádory mozku; diencefalon; prognóza; Child; Infant; dítě; Diencephalon; mužské pohlaví; mladiství; Glioma; Proto-Oncogene Proteins B-raf; předškolní dítě; nádory mozkového kmene; lidé; ženské pohlaví; stupeň nádoru; Humans; kojenec; Prognosis; Mutation; Female; protoonkogenní proteiny B-Raf; Brain Stem Neoplasms